2021
DOI: 10.1038/s41598-021-96990-5
|View full text |Cite
|
Sign up to set email alerts
|

Wood ants as biological control of the forest pest beetles Ips spp.

Abstract: Climate change is one of the major threats to biodiversity, but its impact varies among the species. Bark beetles (Ips spp.), as well as other wood-boring pests of European forests, show escalating numbers in response to the changes driven by climate change and seriously affect the survival of the forests through the massive killing of trees. Many methods were developed to control these wood-boring beetles, however, their implementation can be detrimental for other forest specialists. Ants are widely used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…Further examples have been identified where Crematogaster scutellaris ants inhabiting oak galls reduced fungal infections on oak leaves 24 and weaver ant presence ( Oecophylla longinoda ) in orange trees reduced post‐harvest decay caused by anthracnose and green mould 25 . Although no effect has been found with Formica polyctena in reducing fungal infections of various forest trees, it has been observed that this ant species tended to reduce infections ( P = 0.086) 26 . Lastly, it has been observed that wood ants ( F. polyctena ) used for insect biocontrol in an apple plantation reduced the incidence of both apple brown rot ( Monilia fructigena ) and apple scab ( Venturia inaequalis ) on apples 16 and that the presence of various ant species reduced pear scab ( V. pyrina ) on pear trees 27 …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Further examples have been identified where Crematogaster scutellaris ants inhabiting oak galls reduced fungal infections on oak leaves 24 and weaver ant presence ( Oecophylla longinoda ) in orange trees reduced post‐harvest decay caused by anthracnose and green mould 25 . Although no effect has been found with Formica polyctena in reducing fungal infections of various forest trees, it has been observed that this ant species tended to reduce infections ( P = 0.086) 26 . Lastly, it has been observed that wood ants ( F. polyctena ) used for insect biocontrol in an apple plantation reduced the incidence of both apple brown rot ( Monilia fructigena ) and apple scab ( Venturia inaequalis ) on apples 16 and that the presence of various ant species reduced pear scab ( V. pyrina ) on pear trees 27 …”
Section: Introductionmentioning
confidence: 87%
“…25 Although no effect has been found with Formica polyctena in reducing fungal infections of various forest trees, it has been observed that this ant species tended to reduce infections (P = 0.086). 26 Lastly, it has been observed that wood ants (F. polyctena) used for insect biocontrol in an apple plantation reduced the incidence of both apple brown rot (Monilia fructigena) and apple scab (Venturia inaequalis) on apples 16 and that the presence of various ant species reduced pear scab (V. pyrina) on pear trees. 27 Ants are thus promising biological control agents that may be effective and broadly beneficial in open agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, hybridisation has resulted in male-biased mortality, female heterosis and potential for thermal adaptation (Kulmuni & Pamilo, 2014; Martin-Roy et al, 2021). Understanding hybridisation in the F. rufa group ants is important, since they are keystone species in boreal and mountain forests across Eurasia (Stockan & Robinson, 2016; Trigos-Peral et al, 2021). They build stable nest mounds (Seifert, 2018), and polygynous (i.e., multiple queens per nest) species and populations in particular can reach densities of hundreds of nests per km², as well as impact ecosystem characteristics, ranging from nutrient cycling below ground to aphid farms in the forest canopy.…”
Section: Introductionmentioning
confidence: 99%
“…Instability in the barriers of gene flow has been reported previously (Kulmuni et al, 2020) in this system, suggesting that the balance between the costs and benefits of hybridisation may vary across space and time. Understanding hybridisation in the F. rufa group is important since these ants are keystone species in boreal and mountain forests across Eurasia (Stockan & Robinson, 2016; Trigos‐Peral et al, 2021). They have a significant role in the forest ecosystem: they build stable nest mounds (Seifert, 2018), and populations of polygynous (i.e.…”
Section: Introductionmentioning
confidence: 99%